Countenancing of Light essay and Essay - Imtiaz Hussain; Dr. Sadia Tahir (Zaban-o-Adab, 2021)
The word Inshiya is revealed from the Arabic language with its terminological status. The word Inshiya was originally an official term. It was applied to rough drafts of official decrees and letters and the cleared draft was called writing. It got the name of Diwan and Inshiya. Gradually the word Inshiya was used for writing and arranging decrees and letters. This prose became the language of rules and decrees and letters. In this prose, the element of rhetoric was the main component. This gave rise to the special method of writing which we remember as Insha’iyyah. Insha’Allah is a type of article. That is why there is more closeness between the two. There seems to be a resemblance between the two, but when you look at it, there are many differences that make a difference between the subject and the subject. An article has a form. The article provides potential information on, the topic. While there is no restriction on the subject in the essay, the essayist has the freedom to record other things related to the subject in the middle and add his personal impressions to it.